INVESTIGATING THE FACTORS AFFECTING DRUG-DRUG INTERACTIONS - M.S. SINDHU; B. KANNAN (International Journal of Pharma and Bio Sciences, 2013)
A drug-drug interaction (DDI) is a change in the effect of a drug when administered with another drug or group of drugs. Drug interactions are common and cause increased hospital admission rates, treatment failure, avoidable medical complications, and even deaths. A literature survey is conducted to find factors affecting drug-drug interactions in cohorts that are more likely to be affected by drug-drug interactions. The study found age related factors and multiple drug usage to be reasons for drug-drug interactions, agreeing with previous studies. In addition large cohort studies of general nature were found to be necessary to identify potential DDIs. DDIs being a major concern even in pediatric wards, the methodology of their identification is significantly important to improve pharmacovigilance. The drug interaction checking applications will become more effective if the interactions are correctly identified.